Dysregulated Monocyte and Neutrophil Functional Phenotype in Infants With Neonatal Encephalopathy Requiring Therapeutic Hypothermia - O'Dea, Mary Isabel; Kelly, Lynne; McKenna, Ellen; Melo, Ashanty M.; Ni Bhroin, Megan; Hurley, Tim; Byrne, Angela T.; Colleran, Gabrielle; Vavasseur, Claudine; El-Khuffash, Afif; Miletin, Jan; Murphy, John; et al. (Frontiers in Pediatrics, 2021)
Neonatal encephalopathy (NE) is a significant cause of morbidity and mortality. Persistent inflammation and activation of leucocytes mediates brain injury in NE. The standard of care for NE, therapeutic hypothermia (TH), does not improve outcomes in nearly half of moderate to severe cases, resulting in the need for new adjuvant therapies and immunomodulation holds promise. Our objective was to explore systemic leukocyte phenotype in infants with NE and healthy controls in response to lipopolysaccharide (LPS). 24 infants with NE (NE II-20; NE III=4) requiring TH and 17 term neonatal controls were enrolled and blood samples were analyzed between days one and four of life at a mean(SD) timepoint of 2.1(+/-0.81) days of postnatal life age of at times of routine phlebotomy. Leucocyte cell surface expression levels of Toll-like receptor (TLR)-4, NADPH oxidase (NOX2), CD11b, mitochondrial mass and mitochondrial superoxide production was measured by flow cytometry. Gene expression of TRIF, MyD88 and IRAK4 was measured by RT-PCR. Infants with NE had significantly lower expression of neutrophil CD11b and NOX2 with LPS stimulation compared to healthy term controls. Mitochondrial mass in neutrophils, monocytes was significantly increased in NE infants with LPS compared to controls potentially indicating a dysregulated metabolism. Infants with NE had significantly lower IRAK4 at baseline than controls. NE infants display a dysregulated inflammatory response compared to healthy infants, with LPS hyporesponsiveness to CD11b and NOX2 and decreased IRAK-4 gene expression. This dysregulated immune profile may indicate an adaptable response to limit hyperinflammation.